An enhanced analytical strategy integrating offline two‐dimensional liquid chromatography with high‐resolution accurate mass spectrometry and molecular networking: Comprehensive characterization of HuangLian JieDu Decoction as a case study. Issue 14 (15th May 2022) - Li, Wenjing; Li, Caihong; Sun, Kang; Chi, Chenglin; Li, Zongchao; Xu, Lixiao; Zhao, Yan; Liu, Rongxia
Abstract : Comprehensive ingredient research is of great significance for understanding the effective material basis of herbal medicines, but due to the diversity and complexity of their phytochemicals, such research is challenging. Here, a multifaceted strategy was proposed to analyze and identify the composition of HuangLian JieDu Decoction based on offline two‐dimensional liquid chromatography combined with ultraviolet detection and high‐resolution mass spectrometry. Multiple components were separated by two‐dimensional liquid chromatography, which consisted of hydrophilic interaction chromatography and reversed‐phase liquid chromatography, and then further characterized by high‐resolution mass spectrometry with a full mass spectrometry/precursor ion list/data‐dependent secondary scan data acquisition method. For data processing, database screening and molecular networking were used to identify the components in HuangLian JieDu Decoction. The offline two‐dimensional liquid chromatography combined with ultraviolet detection and a high‐resolution mass spectrometry system showed good orthogonality of 76.35% and a high peak capacity of 5175, effectively separating multiple components. Finally, 527 compounds, including 164 alkaloids, 133 terpenoids, 88 flavonoids, 60 phenylpropanoids, 38 organic acids, and 44 other compounds, were characterized. This integrated approach is suitable for the comprehensive characterization of herbal medicines and other complex chemical systems.